The Implementation of Legal Istinbath Results at LBM MUDI Mesjid Raya Samalanga - Abdullah, Abdullah; Pagar, Pagar; Ardiansyah, Ardiansyah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study explores the application of the LBM MUDI Mesjid Raya's legal istinbath results (jurisprudential reasoning) at Samalanga, focusing on their methods and approaches to legal decision-making. Employing phenomenological and sociological approaches, the research integrates qualitative field and library research to analyze legal phenomena within social and religious contexts. Key participants included the chairman and officials of Lajnah Bahtsul Masail (LBM), as well as scholars from Dayah Mudi Mesra Samalanga, Aceh. Data collection methods comprised in-depth interviews, direct observation, and document analysis. The data were analyzed by using a grounded theory approach, adhering to Miles and Huberman's stages of data reduction, data display, and conclusion drawing. The findings indicated that the approach of LBM MUDI Mesjid Raya is based on a systematic istinbath method and a qauli method that prioritizes classical texts. Their decision-making process incorporates multi-perspective problem analysis, consideration of the legal impact on social, political, and economic dimensions, and alignment with the principles of Ahlu al-Sunnah wa al-Jama'ah. The two stages of discussion, which include both members and leadership, make sure that there is full discussion and careful thought. They do this by combining traditional textual bases with modern situations to uphold the principle of maslahah (public interest). The ilhaq masail bi nadhairiha method generates solutions for issues beyond the scope of classical qauli methods. This illustrates LBM's adaptability in addressing contemporary issues while maintaining a commitment to classical Islamic principles, demonstrating a balance between tradition and modern relevance.